HERFD-XANES probes of electronic structures of ironII/III carbene complexes. Issue 16 (16th April 2020) - Guo, Meiyuan; Prakash, Om; Fan, Hao; de Groot, Lisa H. M.; Hlynsson, Valtýr Freyr; Kaufhold, Simon; Gordivska, Olga; Velásquez, Nicolás; Chabera, Pavel; Glatzel, Pieter; Wärnmark, Kenneth; Persson, Petter; et al.
Abstract : Iron centered N -heterocyclic carbene (Fe-NHC) complexes have shown long-lived excited states with charge transfer character useful for light-harvesting applications. Abstract : Iron centered N -heterocyclic carbene (Fe-NHC) complexes have shown long-lived excited states with charge transfer character useful for light harvesting applications. Understanding the nature of the metal–ligand bond is of fundamental importance to rationally tailor the properties of transition metal complexes. The high-energy-resolution fluorescence detected X-ray absorption near edge structure (HERFD-XANES) has been used to probe the valence orbitals of three carbene complexes, [Fe II (bpy)(btz)2 ](PF6 )2 (bpy = 2, 2′-bipyridine, btz = 3, 3′-dimethyl-1, 1′-bis( p -tolyl)-4, 4′-bis(1, 2, 3-triazol-5-ylidene)), [Fe III (btz)3 ](PF6 )3, and [Fe III (phtmeimb)2 ]PF6 (phtmeimb = [phenyl(tris(3-methylimidazol-2-ylidene))borate] − ). The multiconfigurational restrict active space (RAS) approach has been used to simulate the metal K pre-edge X-ray absorption spectroscopy of these carbene complexes, and have reproduced the metal K pre-edge spectral features in terms of relative intensity and peak positions. The evident intensity difference between the Fe II and the other two Fe III complexes has been elucidated with different intensity mechanisms in the transition. The smaller splitting between the t2g and eg character peak for [Fe III (btz)3 ](PF6 )3 has been observed in the experimental measurements and been reproduced in the RAS calculations. The results show how the combination of experimental HERFD-XANES measurements and ab initio RAS simulations can give quantitative evaluation of the orbital interactions between metal and ligands for such large and strongly interacting systems and thus allow to understand and predict properties of novel complexes.